(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
All over the world, construction and demolition (C&D) waste is generated in enormous amount which leads to various environmental problems. The waste is dumped illegally or into the landfills which degrades the soil and causes pollution. To eliminate the problem of C&D waste management, the concept of zero waste for building construction has been studied in this work. This study aims at finding out the possible research gaps in the management of construction and demolition waste and extant literature survey was done on the sustainability management using zero waste concept.